Carbon-coated aluminum foil coating and preparation method thereof
By designing a multi-level composite conductive network and a bio-based waterborne binder, the contradiction between conductivity and adhesion in carbon-coated aluminum foil coatings was resolved, resulting in carbon-coated aluminum foil coatings with high conductivity and strong adhesion, thereby improving production efficiency and environmental friendliness.
Patent Information
- Application Number
- CN202511460911.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-14
AI Technical Summary
There is a contradiction between existing carbon-coated aluminum foil coatings in terms of improving conductivity and strong adhesion. Traditional processes are cumbersome, have low production efficiency, and the adhesives used pose environmental and safety hazards.
A multi-level composite conductive network design is adopted, which utilizes conductive carbon black to fill the microscopic voids on the surface of aluminum foil, carboxylated multi-walled carbon nanotubes to build conductive bridges, sulfonated graphene oxide to form a layered conductive network, and a dense cross-linked three-dimensional adhesive network is formed by carboxylated cellulose nanocrystals and quaternized chitosan solution. Combined with a bio-based water-based binder, a continuous structural support and attachment network is constructed.
It achieves excellent and uniform conductivity with low filler content, improves adhesion, resolves the contradiction between high conductivity and strong adhesion, and enhances environmental friendliness.
Smart Images

Figure CN120924096A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material technology, specifically relating to a carbon-coated aluminum foil coating and its preparation method. Background Technology
[0002] Aluminum foil is typically used as the current collector in the positive electrode of lithium-ion batteries. However, the adhesion of conventional plain aluminum foil to active materials is weak, and it is prone to detachment during battery fabrication and cycling. At the same time, aluminum foil is prone to forming an oxide film in the electrolyte, increasing interfacial contact resistance and affecting battery performance.
[0003] In recent years, a technology has emerged that coats aluminum foil with a conductive carbon layer. This conductive carbon coating enhances the bonding between the positive electrode coating and the aluminum foil, preventing the active material from detaching. Simultaneously, it forms a conductive transition layer, reducing the internal resistance of the electrode and improving rate performance and cycle life. Currently, various methods exist for preparing carbon-coated aluminum foil, such as sequentially coating the aluminum foil surface with a mixed conductive layer of granular conductive carbon black, sheet-like graphene, and carbon nanotubes. However, these methods involve numerous steps, requiring multiple coating and drying processes, resulting in low production efficiency. Furthermore, the binders used are mostly traditional synthetic polymers, posing environmental and safety risks.
[0004] Regarding conductive agents, existing carbon coatings typically use conductive carbon black as the main component. Its fine particles and high specific surface area provide a certain degree of conductivity. However, conductive networks built solely with carbon black often require a high filler content to achieve good conductivity. Excessive carbon black can increase coating brittleness, reduce adhesion, and even affect the interface smoothness of subsequent positive electrode slurry coating. As for binders, oil-based binders require organic solvents and high-temperature drying, resulting in high volatile organic compound emissions and energy consumption, which are detrimental to the environment and safety. Furthermore, oil-based binders are inherently hydrophobic and inert, limiting their adhesion to metal surfaces. Additionally, the pretreatment of the aluminum foil surface significantly affects coating adhesion. The conventional practice is to clean the aluminum foil surface before carbon coating to remove oil and oxide films, but simple chemical cleaning is unlikely to produce a rough structure conducive to mechanical interlocking.
[0005] In summary, there is still room for improvement in the construction of the conductive network of carbon-coated aluminum foil, the environmental performance of the adhesive, and the surface treatment of the aluminum foil. There is an urgent need for a carbon-coated aluminum foil coating and preparation process that can improve conductivity while also having strong adhesion. Summary of the Invention
[0006] This invention provides a carbon-coated aluminum foil coating and its preparation method, aiming to provide a carbon-coated aluminum foil coating with high conductivity and strong adhesion and its preparation method, thereby solving the contradiction between high conductivity and strong adhesion in current carbon-coated aluminum foil coatings.
[0007] The specific technical solution is as follows: A carbon-coated aluminum foil coating and its preparation method are as follows: S1: Preparation of bio-based waterborne adhesive.
[0008] S11: Microcrystalline cellulose was dispersed in deionized water, and then 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide solution were added dropwise to adjust and maintain the pH of the system at 10. Sodium hypochlorite solution was then added dropwise, and the reaction was carried out at room temperature for 6 hours. The reaction was terminated by adding anhydrous ethanol, and the pH was adjusted to 7. Finally, the precipitate was collected by centrifugation, and the precipitate was dissolved in deionized water and dialyzed to obtain a purified oxidized cellulose suspension. The purified oxidized cellulose suspension was subjected to high-pressure homogenization, ultrasonic disruption, and spray drying to obtain carboxylated cellulose nanocrystals.
[0009] S12: Carboxylated cellulose nanocrystals were mixed with deionized water to prepare a dispersion of carboxylated cellulose nanocrystals.
[0010] S13: Hydroxypropyltrimethylammonium chloride chitosan was mixed with deionized water to prepare a quaternized chitosan solution.
[0011] S14: The carboxylated cellulose nanocrystal dispersion prepared in S12 was added to the quaternized chitosan solution prepared in S13, stirred, and the pH was adjusted to 6.0 to prepare a bio-based aqueous binder.
[0012] S2: Preparation of conductive paste: Sodium polyacrylate and BYK-024 are added to deionized water and stirred until fully dissolved. Then, the mixture is stirred at a low speed of 400 rpm, and the composite conductive agent is added. The mixture is then stirred at a high speed to disperse the mixture and obtain a mixed paste. Finally, the paste is ground until the fineness reaches below 15 μm (detected by a scraper fineness gauge) to obtain a uniform and stable conductive paste.
[0013] S3: Preparation of carbon-coated aluminum foil coating. Under low-speed stirring at 400 rpm, the bio-based water-based binder prepared in S1 is added to the uniform and stable conductive slurry prepared in S2. Then, stirring is continued for 90 min, and the mixture is allowed to stand for 30 min to degas. The viscosity of the coating is then adjusted and the pH of the coating is adjusted to 6.0-7.0. After filtration, the carbon-coated aluminum foil coating is obtained.
[0014] Furthermore, the centrifugal separation described in S11 has the following parameter settings: rotation speed 12000 rpm, duration 15 min.
[0015] The high-pressure homogenizer described in S11 has the following parameter settings: pressure 40MPa.
[0016] The ultrasonic fragmentation parameters described in S11 are: power 600W, on for 2 seconds / off for 1 second, duration 15 minutes.
[0017] Furthermore, the carboxylated cellulose nanocrystals described in S12 account for 1 to 5% of the total solid mass of the binder.
[0018] The deionized water described in S12 is 49 times the mass of carboxylated cellulose nanocrystals.
[0019] The stirring described in S12 has the following parameters: rotation speed 300-800 rpm, duration 2 hours, and temperature 25°C.
[0020] Furthermore, the hydroxypropyltrimethylammonium chloride chitosan described in S13 accounts for 0.5 to 3% of the total solid mass of the binder.
[0021] The deionized water described in S13 has a mass that is 49 times the mass of hydroxypropyltrimethylammonium chloride chitosan.
[0022] The stirring described in S13 has the following parameters: rotation speed 400-600 rpm, duration 4-6 h, and temperature 40-50℃.
[0023] The carboxylated cellulose nanocrystal dispersion described in S14 has a mass ratio of 1:1 to 3:1 with the quaternized chitosan solution.
[0024] Furthermore, the stirring described in S2 has the following parameters: rotation speed 500-800 rpm, duration 5 min.
[0025] The high-speed stirring described in S2 has the following parameters: rotation speed 2000~4000rpm, duration 45~60min, and temperature ≤40℃.
[0026] The composite conductive agent described in S2 comprises conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide, wherein the mass ratio of conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide is (5-15):(1-5):(1-3).
[0027] The composite conductive agent described in S2 has a mass percentage of 10-30%, the dispersant sodium polyacrylate has a mass percentage of 0.5-2.0% of the composite conductive agent, the defoamer BYK-024 has a mass percentage of 0.1-0.5%, and the balance is deionized water; Furthermore, the degassing parameters described in S3 are set as follows: vacuum degree -0.05 to -0.08 MPa.
[0028] The filter screen described in S3 has the following parameter settings: 100-200 mesh.
[0029] The coating described in S3 has the following component mass percentages: bio-based water-based binder solids account for 1-10% of the total mass of the coating, and conductive paste accounts for 90-99% of the total mass of the coating.
[0030] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention utilizes a multi-dimensional composite conductive network design, employing conductive carbon black to fill the microscopic voids on the surface of aluminum foil, carboxylated multi-walled carbon nanotubes to build conductive bridges, and sulfonated graphene oxide to form a layered conductive network, thereby imparting excellent and uniform conductivity to the coating with a relatively low filler content.
[0031] 2. This invention combines carboxylated cellulose nanocrystal dispersion with quaternized chitosan solution, utilizing the electrostatic attraction of positive and negative charges and supplemented by a large number of hydrogen bonds to form a dense cross-linked three-dimensional adhesive network, thereby improving adhesion.
[0032] 3. This invention constructs a continuous conductive network using a composite conductive agent and a continuous structural support and adhesion network using a bio-based water-based binder, thereby achieving dual connectivity of the conductive path and the adhesion interface. Attached Figure Description
[0033] Figure 1 This is a process flow diagram for preparing a carbon-coated aluminum foil coating.
[0034] Figure 2 This is a comparison chart of the surface resistivity and peel strength data of the carbon-coated aluminum foil coatings finally prepared in Examples 1-4 and Comparative Examples 1-3. Detailed Implementation
[0035] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.
[0036] This invention proposes a carbon-coated aluminum foil coating and its preparation method. It solves the contradiction between high conductivity and strong adhesion through a multi-level composite conductive network and a bio-based water-based binder. By precisely compounding zero-dimensional, one-dimensional, and two-dimensional materials, conductivity is improved while reducing the amount of conductive agent used. Furthermore, by compounding modified cellulose nanocrystals with chitosan derivatives, excellent adhesion and processability are ensured while improving environmental friendliness. Specifically: conductive carbon black fills the microscopic voids on the aluminum foil surface, carboxylated multi-walled carbon nanotubes build conductive bridges, and sulfonated graphene oxide forms a layered conductive network, imparting excellent and uniform conductivity to the coating with a low filler content. The carboxylated cellulose nanocrystal dispersion and quaternized chitosan solution utilize electrostatic attraction between positive and negative charges, supplemented by numerous hydrogen bonds, to form a dense, cross-linked three-dimensional adhesive network, improving adhesion while ensuring safety and environmental friendliness. Figure 1 The diagram shows a preparation process for a carbon-coated aluminum foil coating, and its detailed technical solution is as follows: 1. Preparation of bio-based waterborne adhesives 1.1 Preparation of carboxylated cellulose nanocrystal dispersion Microcrystalline cellulose was dispersed in deionized water, and then 2,2,6,6-tetramethylpiperidine-1-oxy radicals and sodium bromide solution were added dropwise to adjust and maintain the pH of the system at 10. Sodium hypochlorite solution was then added dropwise, and the reaction was carried out at room temperature. The pH was adjusted to 10 because a lower pH would result in a slower reaction rate, while a higher pH would cause the sodium hypochlorite solution to undergo disproportionation and become ineffective. Sodium bromide acted as a catalyst. Anhydrous ethanol was added to terminate the reaction, and the pH was adjusted to 7. The mixture was then centrifuged and dialyzed to obtain a purified oxidized cellulose suspension. Dialysis thoroughly removed reaction byproducts and unreacted reagents, yielding a high-purity product. The purified oxidized cellulose suspension was subjected to high-pressure homogenization, ultrasonic disruption, and spray drying to obtain carboxylated cellulose nanocrystals. High-pressure homogenization and ultrasonic disruption were used to dissociate micron-sized oxidized cellulose fibers into nanoscale crystals, while low-temperature drying was used to prevent surface group denaturation or nanocrystal agglomeration of the carboxylated cellulose nanocrystals.
[0037] A 2% (w / w) dispersion of carboxylated cellulose nanocrystals was prepared by stirring and mixing carboxylated cellulose nanocrystals with deionized water. Low-speed stirring can prevent the aggregation of carboxylated cellulose nanocrystals.
[0038] 1.2 Preparation of Quaternized Chitosan Solution Hydroxypropyltrimethylammonium chloride chitosan was mixed with deionized water to prepare a 2% (w / w) quaternized chitosan solution. Low solids content and gentle stirring ensured the full extension of the hydroxypropyltrimethylammonium chloride chitosan molecular chains, preventing entanglement; a temperature ≤50℃ prevented the decomposition of the quaternary ammonium groups.
[0039] 1.3 Preparation of Composite Binder Solution The carboxylated cellulose nanocrystal dispersion prepared above was added to a quaternized chitosan solution, stirred, and the pH was adjusted to 6.0 to prepare a bio-based aqueous binder. Maintaining a weakly acidic pH environment promotes the electrostatic combination of ammonium ions and carboxylate ions, while low-temperature, low-speed stirring prevents phase separation.
[0040] 2. Preparation of conductive paste 2.1 Proportioning The composite conductive agent has a mass percentage of 10-30%, the dispersant sodium polyacrylate has a mass percentage of 0.5-2.0% of the composite conductive agent, the defoamer BYK-024 has a mass percentage of 0.1-0.5%, and the balance is deionized water; wherein, the composite conductive agent contains conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide, and the mass ratio of conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide is (5-15):(1-5):(1-3).
[0041] 2.2 Preparation Sodium polyacrylate and BYK-024 were added to deionized water and stirred until fully dissolved. Then, conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide were added slowly with low-speed stirring to prevent powder from flying and clumping. High-speed stirring was then used to disperse the mixture, resulting in a slurry. High-speed stirring provides high shear force, initially breaking up agglomerates and wetting and initially dispersing the conductive agent. Finally, the slurry was ground until the fineness reached below 15 μm (detected by a scraper fineness gauge), resulting in a uniform and stable conductive slurry. Grinding provides stronger shear and impact forces, thoroughly breaking up agglomerates and ensuring uniform dispersion and sufficient contact of each component, forming a highly efficient conductive network.
[0042] 3. Preparation of carbon-coated aluminum foil coating 3.1 Proportioning The weight percentages of the coating components are as follows: solid bio-based water-based binder accounts for 1-10% of the total weight of the coating, and conductive slurry accounts for 90-99% of the total weight of the coating. The conductive slurry includes: 10-30% composite conductive agent, 0.1-0.5% defoamer BYK-024, 0.5-2% sodium polyacrylate dispersant by weight of composite conductive agent, and the remainder is deionized water.
[0043] 3.2 Preparation Under low-speed stirring, the bio-based water-based binder prepared above is added to the conductive slurry prepared above. Low-speed stirring is beneficial for the binder molecules to uniformly encapsulate and bridge the conductive particles through electrostatic and hydrogen bonding interactions. Then, stirring is continued, and the mixture is allowed to stand to degas. The viscosity of the coating is then adjusted and the pH of the coating is adjusted to 6.0-7.0. The coating is then filtered through a 100-200 mesh filter to obtain a carbon-coated aluminum foil coating. The weak acidity is beneficial to the stability of the composite system, and filtration removes any trace amounts of agglomerates or impurities that may be present.
[0044] Example 1 A method for preparing a carbon-coated aluminum foil coating is as follows: Table 1 Main Raw Materials: S1: Preparation of bio-based waterborne adhesive.
[0045] S11: Microcrystalline cellulose was dispersed in deionized water, and then 2,2,6,6-tetramethylpiperidine-1-oxy radical and sodium bromide solution were added dropwise to adjust and maintain the pH of the system at 10. Sodium hypochlorite solution was then added dropwise, and the reaction was carried out at room temperature for 6 hours. The reaction was terminated by adding anhydrous ethanol, and the pH was adjusted to 7. Finally, the precipitate was collected by centrifugation and dissolved in deionized water for dialysis to obtain a purified oxidized cellulose suspension. The purified oxidized cellulose suspension was subjected to high-pressure homogenization, ultrasonic disruption, and spray drying to obtain carboxylated cellulose nanocrystals. The centrifugation parameters were set as follows: speed 12000 rpm, duration 15 min; high-pressure homogenization parameters were set as follows: pressure 40 MPa; ultrasonic disruption parameters were set as follows: power 600 W, on 2 s / off 1 s, duration 15 min.
[0046] S12: Carboxylated cellulose nanocrystals were mixed with deionized water to prepare a dispersion of carboxylated cellulose nanocrystals. The carboxylated cellulose nanocrystals accounted for 3% of the total solid mass of the binder, and the mass of deionized water was 49 times the mass of carboxylated cellulose nanocrystals. The stirring parameters were set as follows: 550 rpm, 2 h, and 25 °C.
[0047] S13: Hydroxypropyltrimethylammonium chloride chitosan and deionized water were stirred and mixed to prepare a quaternized chitosan solution. The hydroxypropyltrimethylammonium chloride chitosan accounted for 2% of the total solid mass of the binder, and the mass of deionized water was 49 times the mass of hydroxypropyltrimethylammonium chloride chitosan. The stirring parameters were set as follows: 500 rpm, 5 h, and 45 °C.
[0048] S14: The carboxylated cellulose nanocrystal dispersion prepared in S12 is added to the quaternized chitosan solution prepared in S13, stirred, and the pH is adjusted to 6.0 to prepare a bio-based aqueous binder. The mass ratio of the carboxylated cellulose nanocrystal dispersion to the quaternized chitosan solution is 2:1.
[0049] S2: Add sodium polyacrylate and BYK-024 to deionized water and stir until fully dissolved. The stirring parameters are set as follows: 700 rpm for 5 minutes, followed by low-speed stirring at 400 rpm. Then, add conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide sequentially, followed by high-speed stirring to disperse them and obtain a mixed slurry. Finally, grind the slurry until the fineness reaches 10 μm (measured using a scraper fineness gauge) to obtain a uniform and stable conductive slurry. The high-speed stirring parameters are as follows: Settings: Rotation speed 3000 rpm, duration 50 min, temperature 35℃, the mass percentage of composite conductive agent in the conductive slurry is 20%, the dispersant sodium polyacrylate is 1.25% of the mass of composite conductive agent, the mass percentage of defoamer BYK-024 is 0.3%, and the balance is deionized water; wherein, the composite conductive agent contains conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide, and the mass ratio of conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide is 6:2:1.
[0050] S3: Under low-speed stirring at 400 rpm, the bio-based water-based binder prepared in S1 is added to the uniform and stable conductive slurry prepared in S2. Then, stirring is continued for 90 min, and the mixture is allowed to stand for 30 min to degas. The viscosity of the coating is then adjusted and the pH of the coating is adjusted to 6.5. The mixture is then filtered to obtain the carbon-coated aluminum foil coating. The degassing parameters are set as follows: vacuum degree -0.065 MPa. The mass percentage of the coating components is as follows: solid bio-based water-based binder accounts for 8% of the total mass of the coating, and conductive slurry accounts for 92% of the total mass of the coating.
[0051] Example 2 The composition and preparation process are the same as in Example 1, except that: In the preparation process S12, carboxylated cellulose nanocrystals account for 1% of the total solid mass of the binder, and the other components are the same.
[0052] In step S12 of the preparation process, the stirring speed is 300 rpm, and the other steps are the same.
[0053] In the preparation process S13, hydroxypropyltrimethylammonium chloride chitosan accounts for 0.5% of the total solid mass of the binder, and other proportions are the same.
[0054] The stirring parameters in step S13 of the preparation process are set as follows: rotation speed 400 rpm, duration 4 h, temperature 40 °C, and other steps are the same.
[0055] In the preparation process S14, the mass ratio of carboxylated cellulose nanocrystal dispersion to quaternized chitosan solution is 1:1, and other components are the same.
[0056] In the preparation process S2, the composite conductive agent has a mass percentage of 10%, the dispersant sodium polyacrylate has a mass percentage of 0.5% of the composite conductive agent, the defoamer BYK-024 has a mass percentage of 0.1%, and the composite conductive agent has a mass ratio of conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide of 5:1:1, with other components being the same.
[0057] In step S2 of the preparation process, the stirring parameters are set as follows: 500 rpm for speed and 2000 rpm for high-speed stirring. The duration is 45 min and the temperature is 30℃. Other steps are the same.
[0058] In step S3 of the preparation process, the degassing parameters are set as follows: vacuum degree -0.08MPa, pH adjusted to 6.0, and other steps are the same.
[0059] The mass percentages of the coating components in S3 of the preparation process are as follows: the bio-based waterborne binder solids account for 1.5% of the total mass of the coating, the conductive paste accounts for 98.5% of the total mass of the coating, and the other components are the same.
[0060] Example 3 The composition and preparation process are the same as in Example 1, except that: In the preparation process S12, carboxylated cellulose nanocrystals account for 5% of the total solid mass of the binder, and the other components are the same.
[0061] In step S12 of the preparation process, the stirring speed is 800 rpm, and the other steps are the same.
[0062] In the preparation process S13, hydroxypropyltrimethylammonium chloride chitosan accounts for 3% of the total solid mass of the binder, and other proportions are the same.
[0063] The stirring parameters in step S13 of the preparation process are set as follows: rotation speed 600 rpm, duration 6 h, temperature 50 ℃, and other steps are the same.
[0064] In the preparation process S14, the mass ratio of carboxylated cellulose nanocrystal dispersion to quaternized chitosan solution is 3:1, and other components are the same.
[0065] In the preparation process S2, the composite conductive agent accounts for 30% by mass, the dispersant sodium polyacrylate accounts for 2% by mass of the composite conductive agent, the defoamer BYK-024 accounts for 0.5% by mass, and the composite conductive agent contains conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide in a mass ratio of 15:5:3, with other components being the same.
[0066] In step S2 of the preparation process, the stirring parameters are set as follows: rotation speed 800 rpm, high-speed stirring parameters are set as follows: rotation speed 4000 rpm, duration 60 min, temperature 40℃, and other steps are the same.
[0067] In step S3 of the preparation process, the degassing parameters are set as follows: vacuum degree -0.05MPa, pH adjusted to 7.0, and other steps are the same.
[0068] The mass percentages of the coating components in S3 of the preparation process are as follows: the bio-based waterborne binder solids account for 6% of the total mass of the coating, the conductive paste accounts for 94% of the total mass of the coating, and the other components are the same.
[0069] Example 4 The composition and preparation process are the same as in Example 1, except that: In the preparation process S12, carboxylated cellulose nanocrystals account for 4% of the total solid mass of the binder, and the other components are the same.
[0070] In step S12 of the preparation process, the stirring speed is 650 rpm, and the other steps are the same.
[0071] In the preparation process S13, hydroxypropyltrimethylammonium chloride chitosan accounts for 1% of the total solid mass of the binder, and other proportions are the same.
[0072] The stirring parameters in step S13 of the preparation process are set as follows: rotation speed 450 rpm, duration 4.5 h, temperature 48 ℃, and other steps are the same.
[0073] In the preparation process S14, the mass ratio of carboxylated cellulose nanocrystal dispersion to quaternized chitosan solution is 1.5:1, and other components are the same.
[0074] In the preparation process S2, the composite conductive agent has a mass percentage of 25%, the dispersant sodium polyacrylate has a mass percentage of 1.5%, the defoamer BYK-024 has a mass percentage of 1.2%, and the composite conductive agent has a mass ratio of conductive carbon black, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide of 10:2:1, with other components being the same.
[0075] In step S2 of the preparation process, the stirring parameters are set as follows: rotation speed 640 rpm, high-speed stirring parameters are set as follows: rotation speed 2500 rpm, duration 55 min, temperature 37℃, and other steps are the same.
[0076] In step S3 of the preparation process, the degassing parameters are set as follows: vacuum degree -0.06MPa, pH adjusted to 7.0, and other steps are the same.
[0077] The mass percentages of the coating components in S3 of the preparation process are as follows: the bio-based waterborne binder solids account for 7% of the total mass of the coating, the conductive paste accounts for 93% of the total mass of the coating, and the other components are the same.
[0078] Comparative Example 1 The composition and preparation process are the same as in Example 1, except that: In step S1 of the preparation process, the bio-based waterborne binder is removed and replaced with the traditional binder polyvinylidene fluoride; the other steps remain the same.
[0079] Comparative Example 2 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, carboxylated multi-walled carbon nanotubes and sulfonated graphene oxide are removed, and only conductive carbon black is used as the conductive agent. The other steps are the same.
[0080] Comparative Example 3 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, uncarboxylated multi-walled carbon nanotubes and unsulfonated graphene oxide are used instead, while the other steps are the same.
[0081] Based on Examples 1-4 and Comparative Examples 1-3, samples of the final carbon-coated aluminum foil were taken, and the samples were coated onto aluminum foil. The dry film thickness was controlled at 10±1μm, and the coating was baked at 80℃ for 30min. Surface resistivity was then tested, referring to standard GB / T31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity".
[0082] Based on Examples 1-4 and Comparative Examples 1-3, samples of the final carbon-coated aluminum foil coating were taken, and the samples were coated on aluminum foil. The dry film thickness was controlled at 10±1μm, and the coating was baked at 80℃ for 30min. The peel strength test was then performed, referring to the standard GB / T2792-2014 "Test Method for Peel Strength of Adhesive Tapes".
[0083] The specific test results are shown in Table 2. Figure 2 As shown: Table 2 Comparison of core performance between Examples 1-4 and Comparative Examples 1-3: The comparison results above show that Example 1 has the best overall performance. Due to the optimization of the bio-based water-based binder and composite conductive agent, it achieves low surface resistivity and high peel strength, thus resolving the contradiction between high conductivity and strong adhesion. The overall performance of Examples 2 to 4 is slightly lower than that of Example 1, but still remains at a high level. This indicates that the contradiction between high conductivity and strong adhesion can still be resolved under a large range of parameter variations. Comparative Example 1 uses a traditional binder, which has acceptable conductivity, but the adhesion is significantly reduced, failing to meet the requirements for strong adhesion. Comparative Example 2 uses only conductive carbon black, lacking the high conductivity pathways of carbon nanotubes and graphene, resulting in poor conductivity. Comparative Example 3 uses unmodified carbon materials, which have poor dispersibility, leading to poor conductivity and adhesion.
[0084] In summary, it is clear from the above embodiments and comparative examples that the carbon-coated aluminum foil coating provided by the present invention has significantly better surface resistivity and peel strength than traditional solutions. This is attributed to the innovative construction of a bio-based composite adhesive system and a composite conductive agent, which solves the contradiction between high conductivity and strong adhesion.
Claims
1. A carbon-coated aluminum foil coating, characterized in that: The aforementioned carbon-coated aluminum foil coating comprises a conductive slurry and a bio-based waterborne binder. The conductive slurry is composed of a composite conductive agent, a dispersant, a defoamer, and deionized water. The composite conductive agent comprises conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide. The bio-based waterborne binder is formed by a compound of carboxylated cellulose nanocrystals and quaternized chitosan, which combine to form a dense and tough adhesive network layer through electrostatic interactions and hydrogen bonding.
2. The carbon-coated aluminum foil coating according to claim 1, characterized in that: The conductive slurry and the bio-based water-based binder are described, wherein the solids in the bio-based water-based binder account for 1-10% of the total mass of the coating, and the conductive slurry accounts for 90-99% of the total mass of the coating.
3. The carbon-coated aluminum foil coating according to claim 1, characterized in that: The conductive carbon black, carboxylated multi-walled carbon nanotubes, and sulfonated graphene oxide are present in a mass ratio of 5–15:1–5:1–3. The conductive slurry contains a composite conductive agent comprising 10–30% by mass, a dispersant comprising 0.5–2.0% by mass of the composite conductive agent, a defoamer comprising 0.1–0.5% by mass, and the remainder being deionized water.
4. The carbon-coated aluminum foil coating according to claim 1, characterized in that: The carboxylated cellulose nanocrystals account for 1-5% of the total solid mass of the binder, and the quaternized chitosan accounts for 0.5-3% of the total solid mass of the binder.
5. The carbon-coated aluminum foil coating according to claim 1, characterized in that: The carboxylated cellulose nanocrystals are prepared by selective oxidation, using the following raw materials: 2,2,6,6-tetramethylpiperidine-1-oxy radical, sodium bromide, sodium hypochlorite, and microcrystalline cellulose; the 2,2,6,6-tetramethylpiperidine-1-oxy radical is 1% of the mass of the microcrystalline cellulose; the sodium bromide is 10% of the mass of the microcrystalline cellulose; and the sodium hypochlorite is 5 times the mass of the microcrystalline cellulose.
6. The method for preparing the carbon-coated aluminum foil coating according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Preparation of bio-based aqueous binders; S11: Microcrystalline cellulose was dispersed in deionized water, and then 2,2,6,6-tetramethylpiperidine-1-oxy radical and sodium bromide solution were added dropwise to adjust and maintain the pH of the system at 10. Sodium hypochlorite solution was then added dropwise, and the reaction was carried out at room temperature for 6 hours. The reaction was terminated by adding anhydrous ethanol, and the pH was adjusted to 7. Finally, the precipitate was collected by centrifugation, and the precipitate was dissolved in deionized water and dialyzed to obtain a purified oxidized cellulose suspension. The purified oxidized cellulose suspension was subjected to high-pressure homogenization, ultrasonic disruption, and spray drying to obtain carboxylated cellulose nanocrystals. S12: Carboxylated cellulose nanocrystals were mixed with deionized water to prepare a carboxylated cellulose nanocrystal dispersion. S13: Hydroxypropyltrimethylammonium chloride chitosan was mixed with deionized water to prepare a quaternized chitosan solution; S14: The carboxylated cellulose nanocrystal dispersion prepared in S12 was added to the quaternized chitosan solution prepared in S13, stirred, and the pH was adjusted to 6.0 to prepare a bio-based aqueous binder. S2: Preparation of conductive paste: Sodium polyacrylate and BYK-024 are added to deionized water and stirred until fully dissolved. Then, the mixture is stirred at a low speed of 400 rpm, the composite conductive agent is added, and then the mixture is dispersed by high speed stirring to obtain a mixed paste. Finally, the paste is ground until the fineness reaches below 15 μm to obtain a uniform and stable conductive paste. S3: Preparation of carbon-coated aluminum foil coating. Under low-speed stirring at 400 rpm, the bio-based water-based binder prepared in S1 is added to the uniform and stable conductive slurry prepared in S2. Then, stirring is continued for 90 min, and the mixture is allowed to stand for 30 min to degas. The viscosity of the coating is then adjusted and the pH of the coating is adjusted to 6.0-7.
0. After filtration, the carbon-coated aluminum foil coating is obtained.
7. The method for preparing a carbon-coated aluminum foil coating according to claim 6, characterized in that: The centrifugal separation described in S11 has the following parameter settings: rotation speed 12000 rpm, duration 15 min; The high-pressure homogenizer described in S11 has the following parameter settings: pressure 40MPa; The ultrasonic fragmentation parameters described in S11 are: power 600W, on for 2 seconds / off for 1 second, duration 15 minutes.
8. The method for preparing a carbon-coated aluminum foil coating according to claim 6, characterized in that: The deionized water described in S12 is 49 times the mass of carboxylated cellulose nanocrystals; The stirring described in S12 has the following parameters: rotation speed 300-800 rpm, duration 2 hours, and temperature 25°C.
9. The method for preparing a carbon-coated aluminum foil coating according to claim 6, characterized in that: The deionized water described in S13 has a mass that is 49 times the mass of hydroxypropyltrimethylammonium chloride chitosan; The stirring described in S13 has the following parameters: rotation speed 400-600 rpm, duration 4-6 h, and temperature 40-50 °C. The carboxylated cellulose nanocrystal dispersion described in S14 has a mass ratio of 1:1 to 3:1 with the quaternized chitosan solution.
10. The method for preparing a carbon-coated aluminum foil coating according to claim 6, characterized in that: The stirring described in S2 has the following parameters: rotation speed 500-800 rpm, duration 5 min; The high-speed stirring described in S2 has the following parameters: rotation speed 2000~4000rpm, duration 45~60min, and temperature ≤40℃. The degassing described in S3 has the following parameter settings: vacuum degree -0.05 to -0.08 MPa; The filter screen described in S3 has the following parameter settings: 100-200 mesh.
Citation Information
Patent Citations
Conductive carbon slurry, positive electrode slurry, and preparation method and application of conductive carbon slurry and positive electrode slurry
CN114914402A
Multi-element nanocarbon conductive pre-coating modified current collector and preparation method and application thereof
CN116666641A
High-dispersity aluminum foil coating slurry and preparation method thereof
CN116987419A
Silicon-based negative electrode binder, silicon-based negative electrode plate and lithium ion battery
CN117343663A
Graphene carbon nanotube composite conductive paste and preparation method thereof
CN117766196A
Cited By
Water-based carbon-coated aluminum foil coating and preparation method thereof
CN121343484A